CITRA WANITA MODERN DALAM CERPEN UFO GA KUSHIRO NI ORIRU, KAMI NO KODOMOTACHI WA MINA ODORU, THAILAND, DAN HACHI MITSU PAI KARYA HARUKI MURAKAMI - Arsi Widiasih, Ni Luh Putu (Humanis; Volume 15. No.3. Juni 2016)
Woman image always changes with the time. This changes happen because of the time and the community itself. Image of traditional woman and image of modern woman are different because of some issue. Traditional woman always stays at home and take care of her family, while modern woman do an outdoor activity more, and goes to work. To describe about woman image deeply we need to look after the inner and outer of a woman itself. The method that used in this study is dialectic method analysis data. The theory that used in this study is feminist critics by Djajanegara, theory of woman image by Sugihastuti, and theory of self image by Burn. This research result, show some image of modern woman that reflect on the short stories, that image is depend on mentally and physical aspect of the woman figure. The physical image are (1) Japanese woman are wear modern clothes for everyday needed, (2) always take care of their appearance, (3) use a modern hair cut, (4) wear a modern accessories and (5) wear a modern make up style. The mentally image are (1) modern woman is confident, (2) modern woman is brave to show their opinion, (3) modern woman give priority to career, (4) modern woman brave to take a decision, and (5) modern image is well educated. All of those images are made by current condition in the community. Those social conditions are (1) industry and labor, (2) economy prosperity, (3) the change of value, and (4) the government regulation.
Keywords: modern woman, feminist literature, self image